Politicization Of Performance Appraisal Practices : A Case Study In An It Company Based In Selangor - Prema Latha, Subramaniam (Universiti Malaysia Sarawak (UNIMAS), 2020)
Limited study emphasizing on Politicization of Performance Appraisal Practices in an IT industry especially in Malaysia has initiated the strong necessary for this research to be conducted. The specific objectives of this research are to explore the concept of politicization in a private sector, to explore the effects of politicization of performance appraisal on employees’ turnover intention, to discover the effects of politicization of performance appraisal on productivity of employees, to discover challenges encounter by employees due to politicization of performance appraisal and to find out the possible solutions in dealing with the challenges. This research is a qualitative based research adapting a case study research design in an IT Company based in Selangor. There is a total of five informants has been selected based on purposive sampling and interview sessions were conducted to collect relevant data. Researcher used content analysis for this research and summarize it with a simple tree diagram. The main findings for this research revealed that biasness and favouritism make the concept of politicization of performance appraisal to be occurred in a private sector. The findings from this study were an affirmation for Power and Politics Organization Theory and Pfeffer’s Model of Organizational Politics. The implication of this research is that this study will be an eye opener to many people who think that politicization is a small issue and emphasized some strategies to overcome the issues of politicization of performance appraisal which will be beneficial for the management, team leaders and employees for a longer period of time. It is highly recommended for the organization to set a transparent appraisal system and provide necessary training to have a fair evaluation outcome